Consumption Habits of Recorded Music: Determinants of Flamenco Albums Acquisition - Jesús Heredia-Carroza; Luis Palma; Jesús de Sancha-Navarro; Carlos Chavarría-Ortiz (SAGE Open, 2023)
The article analyses the determinants of acquisition of flamenco albums. Flamenco is a musical genre recognized by UNESCO as intangible heritage of humanity. A methodology divided into three phases has been used for this purpose: firstly, interviews with experts from the Spanish music industry where new variables are identified that can affect flamenco consumption habits; then 586 surveys of flamenco spectators who valued these variables and, finally, the application of econometric models to obtain the coefficients of the variables. The results show how the valuation of the composition, the performer and its virtuosity, of the existing trends, and the sociodemographic characteristics of the spectators directly affect the acquisition of flamenco-recorded music. The article contributes to the scarce empirical literature that relates the determinants of recorded music acquisition with traditional popular genres, by adding never studied before variables, focusing on the case of flamenco. JEL Classification: C2; D2; Z1. MSC2010: 00A65; 00A66.